Spatial analysis and risk assessment of heavy metal pollution in rice in Fujian Province, China - Guo, Yourui; Huang, Mingtian; You, Wu; Cai, Luxiang; Hong, Yong; Xiao, Qingtie; Zheng, Xinyu; Lin, Ruiyu (Frontiers in Environmental Science, 2022)
To comprehensively understand the spatial characteristics and pollution hazards of heavy metals in rice in Fujian Province, the contents of Cd, Hg, As, Pb, Cr, Ni, Cu, and Zn in 260 rice samples were measured based on the field investigation. Their spatial distribution patterns and clustering characteristics were explored by geostatistical methods, and their pollution-health risks were revealed by the pollution index method and exposure evaluation model. The results showed that the average contents of eight heavy metals in rice were below the food safety limits, but the excess rates of As, Cu, and Cd samples reached 33.08%, 22.69%, and 18.85%, respectively. In terms of spatial characteristics, the contents of Cd, Hg, and Ni were higher in the southeastern and northwestern regions, while the contents of As, Cu, and Cr were higher in the southwestern parts of Fujian Province. The hotspots of the corresponding heavy metals were also concentrated in the above-mentioned areas, showing an obvious spatial clustering effect. The pollution risk assessment showed that the single factor pollution index of heavy metals in rice decreased in the order of As(0.536) > Hg(0.505) > Cu(0.421) > Cd (0.378) > Cr (0.318) > Zn(0.304) > Pb (0.286) > Ni(0.116) , and the Nemerow comprehensive pollution index was 0.623, which was generally at a safe level with low pollution risk. Furthermore, the non-carcinogenic risk index of heavy metals for adults and children were 3.558 and 6.014, and the carcinogenic risk index were 0.0050 and 0.0084, respectively, with extremely serious health hazards. In contrast, the health damage of heavy metals was higher in children than in adults, with As and Cd in rice as the pivotal elements. Therefore, attention should be paid to the future monitoring and agricultural management of heavy metal pollution in rice in the region.